Pengaruh Marketing Influencer dan Kualitas Produk terhadap Brand Image PT.Abil Mannaf Perkasa pada Tiktok Shop - Putrie Aulya Maulya Sarie; Rizka Aula Assaf (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
The development of social media, particularly TikTok Shop, has transformed digital marketing patterns by providing opportunities for companies to reach consumers directly through influencers. However, excessive promotional practices for SSSKIN products carried out by internal influencers have raised consumer doubts about the authenticity of product claims and impacted brand image. This condition emphasizes the importance of product quality and influencer credibility in shaping brand perceptions in the minds of consumers. This study aims to determine the effect of influencer marketing and product quality on the brand image of PT. Abil Mannaf Perkasa through the TikTok Shop platform. The research method used is quantitative with a descriptive-verification approach. Data were obtained by distributing questionnaires to 95 TikTok users who have purchased SSSKIN products. Analysis was conducted using multiple linear regression, t-test, F-test, and coefficient of determination. The results showed that product quality has a positive and significant effect on brand image, while influencer marketing does not have a significant effect partially. Simultaneously, both variables have a significant effect on brand image formation. These findings confirm that product quality is a major factor determining positive consumer perceptions of a brand, so companies need to maintain product quality consistency to maintain consumer trust and a good brand image.